2018
DOI: 10.1002/slct.201801391
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, In Vitro Evaluation and Docking Studies of Pyrazole‐Thiazole Hybrids as Antimicrobial and Antibiofilm Agents

Abstract: In the present study, a series of novel pyrazole‐thiazole hybrids (4a‐l) were designed, synthesized and assessed for their in vitro antimicrobial activity against both Gram‐positive and Gram‐negative pathogenic bacterial and fungal strains. Compounds derived from p‐CH3 phenyl (4b), p‐Br phenyl (4g), 8‐bromocoumarinyl (4k), and 6,8‐dibromocoumarinyl (4l) exhibited promising inhibitory activity against the tested bacterial strains with minimum inhibitory concentration (MIC)/minimum bactericidal concentration (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Gondru and co-workers adopted the hybridization approach for the design of the new molecules 45a – g ( Table 15 ), which bear simultaneously in one molecular framework the four pharmacophores pyrazole, thiazole, coumarin, and benzothiazole. 100 …”
Section: Antibiofilm Compoundsmentioning
confidence: 99%
“…Gondru and co-workers adopted the hybridization approach for the design of the new molecules 45a – g ( Table 15 ), which bear simultaneously in one molecular framework the four pharmacophores pyrazole, thiazole, coumarin, and benzothiazole. 100 …”
Section: Antibiofilm Compoundsmentioning
confidence: 99%
“…The pyrazole‐containing coumarin–thiazole hybrids 27 (MIC: 1.9 to >125 µg/ml) exhibited considerable activity against S. aureus , B. subtilis , M. luteus , Klebsiella planticola ( K. planticola ), E. coli , and E. aerogenes , and the SAR revealed that the introduction of the second coumarin moiety was also tolerated, as evidenced by hybrids 28 (MIC: 3.9 to >125 µg/ml) that displayed the similar activity. [ 72 ] Three hybrids, 27a,b (MIC: 1.9–7.8 µg/ml) and 28a (MIC: 3.9–7.8 µg/ml), possessed broad‐spectrum activity against all tested strains, but the activity was lower than that of ciprofloxacin (MIC: 0.9 µg/ml). The coumarin–thiadiazole hybrid 29 (inhibition zone: 15.2–17.1 mm), which was also less potent than the references ampicillin (inhibition zone: 23.8–27.4 mm) and ciprofloxacin (inhibition zone: 20.6–23.0 mm), still needs to be modified.…”
Section: Coumarin–thi(adi)azole Hybridsmentioning
confidence: 99%
“…Gondru et al . developed the preparation of pyrazole‐thiazole hybrids ( 216 ) in excellent yield by treating aldehyde ( 215 ) with thiosemicarbazide ( 178 ) and various α ‐bromoketones ( 173 ) under reflux conditions (Scheme ).…”
Section: Synthesis Of Thiazolesmentioning
confidence: 99%